2014
DOI: 10.1177/0194599814541627a61
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Lingual Tonsil Grading System: Interexaminer Agreement

Abstract: Objectives: Comparisons between studies involving the tongue base are limited by the lack of a universal system for grading lingual tonsils. The authors propose a new standardized grading system for lingual tonsil hypertrophy (LTH). Validation was assessed via an interexaminer agreement study. Methods: Video assessment: The proposed grading system consists of a 0 to 4 scale with: 0 = complete absence of lymphoid tissue, 1 = lymphoid tissue scattered over tongue base, 2 = lymphoid tissue covering entirety of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 0 publications
2
46
0
3
Order By: Relevance
“…Los estudios de base de lengua poseen la limitación de que no existe una escala universal aceptada para graduar la HAL 3,21 . Friedman y cols fueron los primeros en desarrollar una escala de clasificación para evaluar la HAL en población pediátrica (Tabla 1).…”
Section: Diagnóstico Diferencialunclassified
See 2 more Smart Citations
“…Los estudios de base de lengua poseen la limitación de que no existe una escala universal aceptada para graduar la HAL 3,21 . Friedman y cols fueron los primeros en desarrollar una escala de clasificación para evaluar la HAL en población pediátrica (Tabla 1).…”
Section: Diagnóstico Diferencialunclassified
“…No se requieren maniobras de colaboración por parte del paciente y es posible realizarlo en corto período de observación 21 . El mismo grupo de autores mencionados, evaluó la correlación interobservador, mediante el análisis por especialistas, a través de imágenes y videos, con resultados satisfactorios 3,21 . Sin embargo, esta escala aún no ha sido validada, ya que no se dispone de una herramienta que sea el estándar de oro, para compararla 21 .…”
Section: Diagnóstico Diferencialunclassified
See 1 more Smart Citation
“…Lingual tonsil hypertrophy (LTH) is a clinical condition often observed in clinical practice during the inspection of the tongue base region . This lymphatic hypertrophy (LH) is implicated in a variety of airway pathologies, ranging from sleep‐related breathing disorders, lingual tonsillitis, and difficult intubation procedures . Additionally, it is frequently a cause of foreign body sensation in the throat and of pharyngodynia in cases of it inflammation …”
Section: Introductionmentioning
confidence: 99%
“…The etiology regarding the growth of this lymphatic tissue (LT) has not been clearly proved . The few studies about this topic showed that previous adenotonsillectomy, laryngopharyngeal reflux (LPR), and a high body mass index could be correlated to LTH, even if defined data regarding this aspect are not available …”
Section: Introductionmentioning
confidence: 99%